Assessment of the Physical Properties of Inclusion Complexes of Forchlorfenuron and γ-Cyclodextrin Derivatives and Their Promotion of Plant Growth - Inoue, Yutaka (ACS Omega, 2018)
[Image: see text] The current study prepared solid dispersions of forchlorfenuron (CPPU) and γ-cyclodextrin (γCD) or CPPU and 2-hydroxypropyl-γ-cyclodextrin (HPγCD) via cogrinding and coprecipitation to assess their physicochemical properties and their effect on plant growth. According to phase solubility diagrams, both CPPU/γCD and CPPU/HPγCD formed an inclusion complex at a molar ratio of 1/1. According to differential scanning calorimetry and powder X-ray diffraction, a ground mixture (GM) of CPPU and γCD (molar ratio = 1/1), a GM of CPPU and HPγCD (molar ratio = 1/1), and a coprecipitate (CP) of CPPU and γCD (molar ratio = 1/1) formed an inclusion complex. According to (1)H–(1)H nuclear Overhauser effect spectroscopy NMR spectroscopy of the GMs and CP, the aromatic rings of the CPPU molecule are presumably included in CD from the wider to the narrower rim of its ring. Cultivation of broccoli sprouts with the GMs and CP resulted in no differences in the length of sprouts in comparison to a commercial preparation (Fulmet).